Traffic into silence: endomembranes and post‐transcriptional RNA silencing - Kim, Yun Ju; Maizel, Alexis; Chen, Xuemei (The EMBO journal, 2014)
Abstract:microRNAs (miRNAs) and small interfering RNAs (siRNAs) are small RNAs that repress gene expression at the post‐transcriptional level in plants and animals. Small RNAs guide Argonaute‐containing RNA‐induced silencing complexes to target RNAs in a sequence‐specific manner, resulting in mRNA deadenylation followed by exonucleolytic decay, mRNA endonucleolytic cleavage, or translational inhibition. Although our knowledge of small RNA biogenesis, turnover, and mechanisms of action has dramatically expanded in the past decade, the subcellular location of small RNA‐mediated RNA silencing still needs to be defined. In contrast to the prevalent presumption that RNA silencing occurs in the cytosol, emerging evidence reveals connections between the endomembrane system and small RNA activities in plants and animals. Here, we summarize the work that uncovered this link between small RNAs and endomembrane compartments and present an overview of the involvement of the endomembrane system in various aspects of RNA silencing. We propose that the endomembrane system is an integral component of RNA silencing that has been long overlooked and predict that a marriage between cell biology and RNA biology holds the key to a full understanding of post‐transcriptional gene regulation by small RNAs